1
$\begingroup$

I do not really know where to start with the following:

Prove that $$\frac{\displaystyle{ \prod_{k = 1}^{2n - 1} k^{\min(k, 2n - k)}}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n - 2k - 1}}}$$ is a power of two.

Could you give me a hint which helps to solve this problem?

$\endgroup$
2
$\begingroup$

Much calculus there :

$$\begin{aligned}\frac{\displaystyle{ \prod_{k = 1}^{2n - 1} k^{\min(k, 2n - k)}}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n - 2k - 1}}} &= \frac{\displaystyle{ \prod_{k = 1}^{n} k^{\min(k, 2n - k)}} \times \prod_{k = n + 1}^{2n - 1} k^{\min(k, 2n - k)}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n - 2k - 1}}} \\ &= \frac{\displaystyle{ \prod_{k = 1}^{n} k^k} \times \prod_{k = n + 1}^{2n - 1} k^{2n - k}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n - 2k - 1}}} \\ &= \frac{\displaystyle{ \prod_{k = 1}^{n} k^k} \times \prod_{k = n + 1}^{2n - 1} k^{2n} \times \prod_{k = 1}^{n - 1}(2k + 1)^{2k + 1}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n}} \prod_{k = n + 1}^{2n - 1} k^{k}} \\ &= \frac{\displaystyle{ \left(\prod_{k = 1}^{n} k^k \right)^2} \times \prod_{k = n + 1}^{2n - 1} k^{2n} \times \prod_{k = 1}^{n - 1}(2k + 1)^{2k + 1}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n}} \prod_{k = 1}^{2n - 1} k^{k}} \\ &= \frac{\displaystyle{ \left(\prod_{k = 1}^{n} k^k \right)^2} \times \prod_{k = n + 1}^{2n - 1} k^{2n}}{\displaystyle{\prod_{k = 1}^{n - 1}(2k + 1)^{2n}} \prod_{k = 1}^{n - 1} (2k)^{2k}} \\ &= \frac{\displaystyle{}\left(\prod_{k = 1}^{2n - 1} k\right)^{2n}}{\displaystyle{}\left(\prod_{k = 1}^{n - 1}(2k + 1)\right)^{2n}} \frac{\displaystyle{ \left(\prod_{k = 1}^{n} k^k \right)^2}}{\displaystyle{} \prod_{k = 1}^{n} k^{2n} \times \prod_{k = 1}^{n - 1} (2k)^{2k}} \\ &= \frac{\displaystyle{ \left(\prod_{k = 1}^{n} k^k \right)^2} \times \prod_{k = 1}^{n - 1}(2k)^{2n}}{\displaystyle{}\prod_{k = 1}^{n} k^{2n} \times \prod_{k = 1}^{n - 1} (2k)^{2k}} \\ &= \frac{\displaystyle{ \prod_{k = 1}^{n} k^{2k}} \times 2^{2n(n-1)}}{\displaystyle{}n^{2n} \times \prod_{k = 1}^{n - 1} (2k)^{2k}} \\ &= \frac{\displaystyle{ } 2^{2n(n-1)}}{\displaystyle{} \prod_{k = 1}^{n - 1} 2^{2k}} \\ &= 2^{n(n-1)} \end{aligned}$$

$\endgroup$
2
$\begingroup$

Let $f(n)$ be the given expression. Then $f(1) = 1$ and $f(n+1)/f(n) = 2^{2n}$:

$$\frac{f(n+1)}{f(n)} = \frac{(n+1)^{n+1}(n+2)^n \dotsb (2n-1)^3(2n)^2(2n+1)}{3^{2n-1} \dotsb (2n-1)^3(2n+1)} \cdot \frac{3^{2n-3} \dotsb (2n-1)}{(n+1)^{n-1}(n+2)^{n-2} \dotsb (2n-1)}$$ which simplifies to $$\frac{f(n+1)}{f(n)} = \frac{(n+1)^2(n+2)^2 \dotsb (2n-1)^2(2n)^2}{3^2 \dotsb (2n-1)^2} = \frac{(n+1)^2(n+2)^2 \dotsb (2n-1)^2(2n)^2 2^2 4^26^2\dotsb (2n)^2} {3^2 \dotsb (2n-1)^2 2^2 4^26^2\dotsb (2n)^2} = \frac{2^{2n} (2n)!^2}{(2n)!^2} = 2^{2n}$$

Then $$f(n) = f(1)\cdot \frac{f(2)}{f(1)} \dotsb \frac{f(n)}{f(n-1)} = 2^{2\cdot 0} \cdot 2^{2\cdot 1} \dotsb 2^{2\cdot (n-1)} = 2^{2(1+2+\dotsb (n-1))} = 2^{n(n-1)}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.